2022
DOI: 10.3390/app12020675
|View full text |Cite
|
Sign up to set email alerts
|

Laser Reconstruction of Spinal Discs Experiments and Clinic

Abstract: Degenerative disease of the intervertebral discs (DDD) is currently a serious problem facing the world community. The surgical methods and conservative therapy used today, unfortunately, do not stop the pathological process, but serve as a palliative method that temporarily relieves pain and improves the patient’s quality of life. Therefore, at present, there is an active search for new methods of treating DDD. Among new techniques of treatment, biological methods, and minimally invasive surgery, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Studies indicate that PBM affects the proliferation and differentiation of muscle cells. Baskov et al (2022) [27] cited that the influence of nearinfrared light on ATP activation and cell proliferation occurs through the interaction of photons with intracellular water layers. However, the wide range of parameters used in terms of output power, wavelength, type of emission, radiant exposure, irradiation time, dosage, total energy delivered, application method, and interval between sessions has led to different results among the studies found in the literature [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that PBM affects the proliferation and differentiation of muscle cells. Baskov et al (2022) [27] cited that the influence of nearinfrared light on ATP activation and cell proliferation occurs through the interaction of photons with intracellular water layers. However, the wide range of parameters used in terms of output power, wavelength, type of emission, radiant exposure, irradiation time, dosage, total energy delivered, application method, and interval between sessions has led to different results among the studies found in the literature [28].…”
Section: Discussionmentioning
confidence: 99%
“…One of such methods is the use of laser radiation in spinal surgeries. Laser reconstructive surgery in degenerativedystrophic damages of the spine was successfully used with lasers at the wavelengths of 1.56 [11] and 0.97 µm [12].…”
Section: Introductionmentioning
confidence: 99%